2022
DOI: 10.1186/s13059-022-02638-6
|View full text |Cite
|
Sign up to set email alerts
|

LAP2α preserves genome integrity through assisting RPA deposition on damaged chromatin

Abstract: Background Single-stranded DNA (ssDNA) coated with replication protein A (RPA) acts as a key platform for the recruitment and exchange of genome maintenance factors in DNA damage response. Yet, how the formation of the ssDNA-RPA intermediate is regulated remains elusive. Results Here, we report that the lamin-associated protein LAP2α is physically associated with RPA, and LAP2α preferentially facilitates RPA deposition on damaged chromatin via phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 84 publications
(81 reference statements)
1
7
0
Order By: Relevance
“…These results indicate that SIRT7 and LAP2α knockout cause chromosome instability. LAP2α maintains genomic integrity by aiding RPA deposit on damaged chromatin 54 , and this result is consistent with the experimental results. Moreover, our results showed that SIRT7 regulates chromatin stabilization by directly binding to LAP2α protein in cancer cells.…”
Section: Discussionsupporting
confidence: 91%
“…These results indicate that SIRT7 and LAP2α knockout cause chromosome instability. LAP2α maintains genomic integrity by aiding RPA deposit on damaged chromatin 54 , and this result is consistent with the experimental results. Moreover, our results showed that SIRT7 regulates chromatin stabilization by directly binding to LAP2α protein in cancer cells.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, Ir-CA could overcome the cisplatin resistance of A549R cells (Table ). GSEA revealed that the gene set of drug metabolism-cytochrome associated with platinum drug resistance has been dramatically regulated as the down-regulation of cisplatin detoxification GSTP1 (glutathione S-transferase P1) and GSTM4 (glutathione S-transferase M4) (Figure C,G). , DNA repair systems were also deactivated after the Ir-CA treatment, as the expressions of genes PCNA, RPA1, RPA2, RPA3, and PARP1 were down-regulated (Figure C). , This would facilitate the understanding of the mechanism for the capacity to overcome cisplatin resistance of Ir-CA .…”
Section: Resultsmentioning
confidence: 95%
“…45,46 DNA repair systems were also deactivated after the Ir-CA treatment, as the expressions of genes PCNA, RPA1, RPA2, RPA3, and PARP1 were down-regulated (Figure 3C). 47,48 This would facilitate the understanding of the mechanism for the capacity to overcome cisplatin resistance of Ir-CA.…”
Section: Occurrence Of Mitophagy and Cell Cycle Arrestmentioning
confidence: 99%
“…While a recent study reported that LAP2α could associate with Replication Protein A (RPA) and facilitate its deposition to damaged chromatin during homologous recombination 35 . However, our ndings reveal a distinctive occurrence at telomere, that the disruption of LAP2α increases the recruitment of RPA to telomeric DNA.…”
Section: Discussionmentioning
confidence: 99%